IMPLEMENTASI NILAI-NILAI QURANI PADA PEMBELAJARAN MEMBACA HURUF HIJAIYAH DI PAUD ISLAM - Fatliha Nurhasanah; Lilis Lisnawati; Santi Nurul Aryanto (JOURNAL SAINS STUDENT RESEARCH, 2026)
Quranic learning in Islamic Early Childhood Education (PAUD) is an effort to instill Islamic values ​​from an early age through an approach appropriate to children's developmental stages. This study aims to describe the concepts, stages, methods, and role of Quranic learning in developing Islamic character in early childhood. The research method used is a literature review, analyzing various books and scientific articles relevant to Quranic learning and Islamic Early Childhood Education (PAUD). The results of the study indicate that Quranic learning can be integrated into the PAUD curriculum through the introduction of the hijaiyah alphabet, memorization of short surahs, the practice of prayer and etiquette, and methods such as Iqro' and Tilawati. This learning not only develops children's cognitive abilities but also forms Quranic character traits such as honesty, patience, compassion, and responsibility through contextual and interactive activities.